SUFISM IN THE PERSPECTIVE OF THE QUR'AN AND HADITH - Nurul Azizah; M. Aris Faisol (TAWASUT, 2020)
Abstract An understanding of the inner element is also called Sufism. It is from the Qur'an and the Sunnah that the Sufis first base their opinions on morals and behavior, longing and love for God, makrifat, suluk (path), as well as spiritual practices. This research is library research that aims to analyze "Sufism in the perspective of the Qur'an and Hadith". The results of this study indicate that Sufism and Sufism have a certain position in the Islamic environment. The main teachings of Sufism when viewed in terms of its basics both from the Qur'an and Hadith, it can be found that Sufism teaches zuhudan to the world and complete surrender only Allah alone and make Him the highest love above all love. Key Word: Sufism, Al-Qur'an, Hadith Abstrak Pemahaman terhadap unsur yang bersifat batiniah disebut juga tasawuf. Dari Al-Qur’an dan As Sunnah itulah, para sufi pertama-tama mendasarkan pendapat-pendapat mereka tentang moral dan tingkah laku, kerinduan dan kecintaan pada Ilahi, makrifat, suluk (jalan), dan juga latihan-latihan rohaniah. Penelitian ini merupakan penelitian Library research yang bertujuan untuk menganalisis “Tasawuf dalam perspektif al-Qur’an dan Hadis”. Hasil penelitian ini menunjukkan bahwa tasawuf dan sufi memiliki posisi tertentu dalam lingkungan Islam Adapun ajaran utama dari tasawuf jika dilihat dari segi dasar-dasarnya baik dari al-Qur'an maupun hadis, maka dapat ditemukan bahwa tasawuf mengajarkan kezuhudan terhadap dunia dan penyerahan diri sepenuhnya hanya kepada Allah semata dan menjadikan-Nya kecintaan tertinggi di atas segala cinta. Kata Kunci: Tasawuf, al-Qur’an, Hadis